Equine Influenza and Tetanus Immunisation: Evaluation of Antibody Response and Safety of Equip® FT and Equip® F Administration after Reduction of the Primary Course Interval to 3 Weeks. (9th September 2013) - Paillot, R.; Ons, E.; Besognet, B.; Slootmans, N.; Thomas, A.; Salt, J.
Abstract : Aims: A 6‐week interval is currently recommended during the primary course of the equine influenza (EI) vaccines Equip® FT or Equip® F. This study aimed to evaluate immunogenicity and safety of a 3‐week accelerated interval in order to improve flexibility and to reduce the period of susceptibility to EI virus (EIV) infection. Methods: Three groups of 10 ponies were respectively vaccinated with the vaccine Equip® FT according to the recommended 6‐week V1–V2 interval (T02), Equip® F or Equip® FT according to an experimental accelerated 3‐week interval (T03 and T04, respectively). These groups were boosted (V3) with Equip® F 5 months after V2. Ten ponies in a control group were injected with saline (T01). The antibody response to the vaccine antigens (tetanus toxoid and EIV) were measured 2 weeks after V2 and V3 with the toxin binding inhibition test (ToBI) and single radial haemolysis (SRH), respectively. All animal work received ethical approval. Results: The accelerated schedule of immunisation was well tolerated. At both time points, in all vaccinated groups, SRH least squares means for A/eq/Borlange/91 and A/eq/Kentucky/98 antigens were well above 85 mm 2, a level described previously to provide clinical protection against homologous EIV strains. Non inferiority of SRH least square means were demonstrated at 2 weeks post V2 for both antigens for T03 and T04, and for A/eq/Kentucky/98 antigen in group T04 after V3. For tetanus, ToBI least squares means were 86.3 iu/mI for T02 and 45.9 iu/ml for T04 after V2 and 2.6 iu/ml for T02 and 2.2 iu/ml for T04 after V3. A level of 0.02 iu/ml has been described as being protective in various publications. Conclusion and practical relevance: A 3‐week accelerated primary course interval was well tolerated and serology results suggested good immunogenicity. Ethical animal research: The study was conducted under the Animal Health Trust Home Office Project License and with approval of the Zaventem Ethics Review Assessment team (Zoetis).Sources of funding: The study was sponsored by Pfizer/Zoetis Animal Health.Competing interests: Equip® FT is owned by Zoetis, who sponsored this study. Romain Paillot reports no conflict of interest. All other authors are employed by the study sponsor.